Perancangan Sistem Informasi Akuntansi Penjualan Dan Pencatatan Hutang pada Toko Elektronik XYZ Salatiga - Suharyadi (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2022)
For an organization, speed and accuracy in obtaining information has become a necessity. The existence of an information system becomes a necessity to solve the problem of speed and accuracy in accessing information. XYZ Electronic Store before implementing the information system, had difficulty in knowing quickly and accurately about sales information and how much the store's debt had not been paid. The research method used in this research is observation, interviews and design and implementation of the system. Design system design with DFD, ERD and implementation with PHP programming language. Design system design with the prototype method. After implementing the sales accounting information system and debt recording, the problems faced by XYZ Electronic Store can be resolved. Information on the number of sales in a certain period can be quickly identified, and can schedule debt payments. Debt payment time can be set because the system records all complete debt lists along with the due date.